Indices of refraction in children with pseudophakia predisposed to abnormal refractive error changes after congenital cataract extraction - L. S. Khamraeva; D. U. Narzullaeva; L. A. Katargina; T. B. Kruglovà (Российский офтальмологический журнал)
Purpose. To study refractive indices in children with a predisposition to myopia and hyperopia after congenital cataract extraction and IOL  implantation.Material  and methods. 60 children (95 eyes) aged 1 to 12 years were examined  for refraction error 30–36 months after congenital cataract extraction and IOL implantation. The examination  included case history data to find out whether the children were  predisposed to myopia or hyperopia before IOL implantation.Results. Refraction increase in pseudophakia is observed both in and beyond the risk group. Myopia and emmetropia disproportionate to age were manifested in most children with a predisposition to myopia (70.2 %). The authors believe that abnormal refractive changes may be a result of inadequate selection of IOL  optical power, explained by the fact that it is calculated by a universal formula irrespective of the risk of abnormal refraction changes in children and specific biometry in the risk group. The high frequency of unplanned refraction in case of pseudophakia  in children predisposed to abnormal refractive changes is probably due to either obscuration and refractive amblyopia.Conclusion. In children at risk of abnormal refractive changes, it is advisable to determine an individual  correction coefficient for the formula calculating IOL  power prior to IOL  implantation, to correct residual refraction and to treat amblyopia.